The politics of numbers. Framing intra-EU migrants in the Netherlands. Issue 4 (2nd October 2017) - van Ostaijen, Mark; Scholten, Peter
ABSTRACT: Numbers and data collection play a key role in political framing. To explore how this works, this article provides a case-study analysis of European mobile workers in the Netherlands. Following the increase of intra-European mobility, European mobile workers have emerged as an important but contested policy target group for receiving countries. This article examines how numbers contributed to the framing process of this topic. This study reveals how frames legitimize the strategic usage of numbers and the indication of issues as problems. This contributes to our understanding of the importance of numbers in the framing process of target groups.